Halichoerus Nilsson 1820 - W. Christopher Wozencraft (Smithsonian Institution Press, 1993)
Halichoerus Nilsson, 1820. Skand. Faun. Dagg. Djur., 1:376. TYPE SPECIES: Halichoerus griseus Nilsson, 1820 (= Phoca grypus Fabricius, 1791). COMMENTS: Mohr (1952) described successful mating in captivity between Phoca hispida and Halichoerus grypus. Published as part of W. Christopher Wozencraft, 1993, Order Carnivora, pp. 279-348 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 329, DOI: 10.5281/zenodo.7359191